Pro Bash programming scripting the GNU/Linux shell - Johnson, Chris F. A. (The expert's voice in Linux, 2009)
"The bash shell is a complete programming language, not merely a glue to combine external Linux commands. By taking full advantage of shell internals, shell programs can perform as snappily as utilities written in C or other compiled languages"--Resource description page